2015
DOI: 10.1016/j.ctcp.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tai Chi Chuan on balance in women with multiple sclerosis

Abstract: The results suggest that Tai Chi Chuan could be used as a safe complementary intervention to increase balance in patients with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…The present study was consistent with the results of Azimzade and co-worker (2015) that investigating the effect of Tai Chi training on balance of women with MS, which showed that Tai Chi exercise as a complementary therapeutic method had a significant effect on increasing balance of patients with MS after 8 weeks (Azimzadeh et al, 2015). The improvement was considered to reflect the effect of exercises on increased neuromuscular adaptations, improved function of vestibular system and vision as well as enhanced deep sense.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study was consistent with the results of Azimzade and co-worker (2015) that investigating the effect of Tai Chi training on balance of women with MS, which showed that Tai Chi exercise as a complementary therapeutic method had a significant effect on increasing balance of patients with MS after 8 weeks (Azimzadeh et al, 2015). The improvement was considered to reflect the effect of exercises on increased neuromuscular adaptations, improved function of vestibular system and vision as well as enhanced deep sense.…”
Section: Discussionsupporting
confidence: 92%
“…Tai Chi is a type of Chinese martial art involving movements at low rates, gentle rotation of organs, opening and closing joints, and performing movements in weight bearing conditions. Tai Chi exercises put a high emphasis on respiratory techniques, which enhances performance in people (Azimzadeh et al, 2015). Movements of Tai Chi exercise require balance, stability, and movement of joints.…”
Section: Introductionmentioning
confidence: 99%
“…Tai Chi is a complementary therapy, in recent years, non-pharmacological methods have attracted the attention of patients and health care providers (Azimzadeh et al 2013). In elderly nursing, since a holistic look and attention to all the needs of an elderly person is very much important; therefore, implementation of this exercise can promote the health of the geriatrics and find a clear or effective form for this sport in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Tai Chi is a traditional Chinese mind-body exercise. In Tai Chi, smooth and rhythmic movements are linked, causing the transfer of body weight from one leg to other resulting in better balance (Lan et al 2013).Tai Chi exercise has several forms that vary in different situations (Azimzadeh, Hosseini & Nourozi Tabrizi 2013). A simplified 8-form program of Tai Chi which is derived from a complex 24-form, allows the elderlies to perform it either by standing or sitting, and let them enjoy Tai Chi exercise without having to worry about remembering different movements, an important method of controlling their stress (Lee 2017).One of the researches on Tai Chi exercise conducted by Taylor-Piliae (2014) showed that Tai Chi Quan is a safe form of exercise to prevent and manage cardiovascular disease with no side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Dance and martial arts such as Tai Chi have been found to be effective at improving gait and balance in MS and various neurologic populations. [38][39][40][41] Wearable technology ("wearables"), such as activity trackers worn on the wrist or hip, have the potential for evaluating the effectiveness of interventions and providing feedback to the provider as well as the patient.…”
Section: Managementmentioning
confidence: 99%